Abstracts of Papers Presented at the 1997 AFA Meeting: Author Index of the Abstracts (Journal of Finance, 1997)
s of Papers Presented at the 1997 AFA Meeting: Author Index of the Abstracts, The Journal of Finance, Vol. 52, No. 3, Papers and Proceedings Fifty-Seventh Annual Meeting, American Finance Association, New Orleans, Louisiana January 4-6, 1997 (Jul., 1997), pp. 1199-1260